Impact of Organized Retailing on the Unorganized Sector - Mathew Joseph (Indian Council for Research on International Economic Relations (ICRIER), 2008)
The retail business, in India, is estimated to grow at 13 per cent per annum from US 322 billion in 2006-07 to US 590 billion in 2011-12. The unorganized retail sector is expected to grow at about 10 per cent per annum from US 309 billion 2006-07 to US 496 billion in 2011-12. Organized retail which now constitutes a small four per cent of retail sector in 2006-07 is likely to grow at 45-50 per cent per annum and quadruple its share of total retail trade to 16 per cent by 2011-12. The study, which was based on the largest ever survey of all segments of the economy that could be affected by the entry of large corporates in the retail business, has found that unorganized retailers in the vicinity of organized retailers experienced a decline in sales and profit in the initial years of the entry of organized retailers. The adverse impact, however, weakens over time. The study has indicated how consumers and farmers benefit from organized retailers. The study has also examined the impact on intermediaries and manufacturers. The results are indicative of the mega-and-minimetro cities around a limited number of organized retail outlets. Based on the results of the surveys, the study has made a number of specific policy recommendations for regulating the interaction of large retailers with small suppliers and for strengthening the competitive response of the unorganized retailers.
Keywords: L81; Q13; 330; Retail Sector; Organised Retail; Unorganised Retail; Kirana store; Food Supply Chain